Distribution of Aspergillus Species and Prevalence of Azole Resistance in Respiratory Samples From Swiss Tertiary Care Hospitals. (18th December 2021) - Ragozzino, Silvio; Goldenberger, Daniel; Wright, Patrick R; Zimmerli, Stefan; Mühlethaler, Konrad; Neofytos, Dionysios; Riat, Arnaud; Boggian, Katia; Nolte, Oliver; Conen, Anna; Fankhauser, Hans; Schreiber, Peter W; et al.
Abstract: Among 400 Aspergillus species from respiratory samples in Switzerland, Aspergillus fumigatus was the most frequent species. Non- fumigatus Aspergillus spp were more prevalent among solid organ transplant recipients and after azole exposure. Azole resistance was detected in 4 A fumigatus isolates, 3 of them with the "environmental" mutation TR34 /L98H in the cyp51A gene.